Composite materials formation for orthopaedic implants - Avilov, A.M.; Deryuga, V.A.; Popov, G.F.; Popova, N.G.; Rudychev, V.G.; Shkilev, A.L. (Вопросы атомной науки и техники, 2004)
One of most up-to-date problems of orthopaedy is the development of new materials for replacement of osseous tissue and cartilage defects. Electron beam (EB) processing of polymer composites with bioactive ceramics has been used for manufacture of artificial materials for orthopaedic implants. Experimental approaches and problems of EB processing of composites based on ultra-high-molecular weight polyethylene (UHMWPE) are discussed. Однією з актуальних задач в ортопедії є пошук і розробка нових штучних матеріалів для заміщення кісткової тканини і хряща. Обробка полімерних композиційних матеріалів з біоактивною керамікою електронними пучками використовувалась для виготовлення штучних матеріалів ортопедичного призначення. Приводяться експериментальні досягнення і проблеми радіаційної технології отримання композитів на основі надвисокомолекулярного поліетилену. Одной из актуальных задач в ортопедии является поиск и разработка новых материалов для замены костной ткани и хряща. Обработка полимерных композиционных материалов с биоактивной керамикой электронными пучками использовалась для изготовления искусственных материалов для ортопедических имплантатов. Обсуждаются экспериментальные достижения и проблемы радиационной технологии обработки композитов на основе сверхвысокомолекулярного полиэтилена.